Discourses and conflicts in water resources management: farmers, environmentalism and sustainability. Contribution from social anthropology to water governance - Zamora Acosta, Elías; Acosta Naranjo, Rufino (Revista de Antropología Social, 2011)
The goal of this paper is to present some of the results of a project commissioned by the Ministry of Environment of the Government of Spain and the Confederación Hidrográfica del Guadalquivir to develop a participatory process aimed at drafting the rules that would govern the use of a groundwater located in the subsoil of a region of Western Andalusia, following the guidelines contained in the Water Framework Directive of the European Union. The paper presents and analyzes the discourses, and the logics underlying them, of the farmers and representatives of associations of environmental focus in the area about the uses and current status of the water resources and its impact on water conservation and the ecosystem that it is part. It also argues about the way that social anthropology can contribute to consensus building and implementation of a new governance of water by public agencies.